2019
DOI: 10.1371/journal.pone.0213986
|View full text |Cite
|
Sign up to set email alerts
|

Salt tolerance in indica rice cell cultures depends on a fine tuning of ROS signalling and homeostasis

Abstract: Among cereal crops, salinity tolerance is rare and complex. Multiple genes control numerous pathways, which constitute plant’s response to salinity. Cell cultures act as model system and are useful to investigate the salinity response which can possibly mimic a plant’s response to stress. In the present study two indica rice varieties, KS-282 and Super Basmati which exhibited contrasting sodium chloride (NaCl) stress response were used to establish cell cultures. The cell cultures showed a contrasting response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 77 publications
1
20
0
1
Order By: Relevance
“…Also, excessive Na + depolarizes the plasma membrane, thereby increasing Ca 2+ influx and activating signaling responses, consequently minimizing Na + uptake, increasing Na + sequestration, and extrusion as well as restoring K + levels (Reddy, Kim, Kim, et al, 2017; Wang, Li, Wei, et al, 2012). ROS‐induced Ca 2+ influx in response to salt stress has also been reported by Ijaz et al (2019). Genes involved in potassium homeostasis are reported to play a dynamic role in salinity tolerance in rice (Ijaz et al, 2017).…”
Section: Role Of No and H2s Under Salt Stresssupporting
confidence: 69%
“…Also, excessive Na + depolarizes the plasma membrane, thereby increasing Ca 2+ influx and activating signaling responses, consequently minimizing Na + uptake, increasing Na + sequestration, and extrusion as well as restoring K + levels (Reddy, Kim, Kim, et al, 2017; Wang, Li, Wei, et al, 2012). ROS‐induced Ca 2+ influx in response to salt stress has also been reported by Ijaz et al (2019). Genes involved in potassium homeostasis are reported to play a dynamic role in salinity tolerance in rice (Ijaz et al, 2017).…”
Section: Role Of No and H2s Under Salt Stresssupporting
confidence: 69%
“…This is metabolized by ROS scavenger like cytochrome P450 to prevent cellular damages, ultimately leading to redox homeostasis. Studies suggest that production of ROS varies during abiotic stress response between sensitive and tolerant varieties of rice [66][67][68]. Zhang et al have shown that rice can better adapt to the chilling stress condition when ROS-mediated signaling genes were upregulated.…”
Section: Discussionmentioning
confidence: 99%
“…Plasma membrane RBOHs play a key role in signal transduction reactions that mediate plant acclimation to abiotic stresses, since they are the primary sites of ROS production at the apoplast during abiotic stress condition [19]. We recently demonstrated a pivotal role for innate ROS scavenging systems and NOXs in fine tuning the intracellular H 2 O 2 signalling and inducing salt-tolerance, both at the plant and single cell level [32,47,115]. Similarly, Saini and co-workers [35] observed a higher expression level of OsNOX3 in the roots of a salt-tolerant cultivar than in those of a salt-sensitive genotype.…”
Section: Resultsmentioning
confidence: 99%